Phonological awareness program at school for children with Specific Language Disorders and the role of ICTs - Gkora, Vana; Stathopoulou, Agathi (Eximia, 2022)
The aim of the present study is to implement an intervention program in phonological awareness and verbal working memory in a student with Special Learning Difficulties and to improve the student's cognitive abilities by making a before and after comparison. For the purpose of the present study used the Raven CPM scale, the WISC III, and the Athena Test as psychometric tools to assess the student. The intervention procedure lasted 4 weeks and the student attended 20 sessions for 45 minutes each day. All the activities given to the student were implemented through audio presentation or image presentation. At the end of the intervention, the student was re-evaluated and showed higher scores than the initial evaluation, thus revealing the positive results of an intervention program and showing that there is a relationship between working memory and phonological awareness. These results underline the importance of an appropriate intervention program and show that if it aims at enhancing phonological awareness and utilizes multisensory methods, can improve the levels of working memory that are necessary for the perception and the understanding of language structures, and finally the enhancement of the final acquisition of language.